The study of the respiratory activities of prostate cancer DU145 cells under acidic pH (Experimental biology, 2016)
Acidic pH is toxic to many cells, including tumors. However, if tumors have successfully adapted to their condition, and use it for their own cellular activation, thisincreases drug resistance and leads to more aggressive behavior. Therefore, management of tumor pH and inhibitionof blockade of proton-sensing system are importantin not only raising drug efficacy, e.g. mitoxantrone, but inpreventing metastasis. Recent advances in cancer research have revealed a significant contribution of the tumorigenic microenvironment to metabolic reprogramming of tumors. Prostate cancer cells rearrange their metabolism, so that they support their elevated oxidative phosphorylation and promote a cancer friendly tumor microenvironment. This work aimed to study the respiratory activities of prostate cancer DU145 cells under acidic pH mimicking the tumorigenic microenvironment condition. The respiratory and oxidative phosphorylation abilities of prostate cancer DU145 and other cells were studied by high-resolution respirometry. An important finding was that prostate cancer cells in an environment at pH 6.8 are capable of consuming TCA cycle intermediates, such as succinate, citrate and others, available in extracellular fluids, while physiological pH 7.4 was not favorable for this process.This process could yield novel targets for anti-cancer therapy and has the potential to be used for imaging-based diagnostics to identify non-glycolytic tumors.
Keywords: prostate cancer; mitochondria respiration; oxidative phosphorylation; acidic tumor microenvironment; succinate.